2020
DOI: 10.1089/whr.2019.0020
|View full text |Cite
|
Sign up to set email alerts
|

Empowerment and HIV Risk Behaviors in Couples: Modeling the Theory of Gender and Power in an African Context

Abstract: Background: Young women and girls in Eastern and Southern Africa are at elevated risk of acquiring human immunodeficiency virus (HIV) compared with men, largely due to power dynamics within heterosexual relationships that contribute to HIV risk behaviors. Few studies employ a comprehensive framework to examine divisions between men and women and HIV risk behaviors in an African context. Thus, we examined associations between levels of women's empowerment and HIV risk behaviors applying the Theory of Gender and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…This provides support for the higher contraceptive use found among empowered women in many existing studies [ 28 – 30 , 33 , 34 ]. It may also account for a higher ability to negotiate safer sex as reported in some studies [ 32 , 35 ].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This provides support for the higher contraceptive use found among empowered women in many existing studies [ 28 – 30 , 33 , 34 ]. It may also account for a higher ability to negotiate safer sex as reported in some studies [ 32 , 35 ].…”
Section: Discussionmentioning
confidence: 94%
“…Studies have also linked a lack of autonomy in sexual relations to other adverse health outcomes such as mental health challenges [26], and newborn and infant morbidity [27]. Three, it also reflects the level of women's empowerment in society, which numerous studies [28][29][30][31][32][33][34] have found to strongly impact contraceptive use, and the ability to negotiate safer sex [35]. It is reasoned that through empowerment, women's autonomy and agency improve.…”
Section: Introductionmentioning
confidence: 99%
“…Women who are empowered can make independent decisions regarding their health, including HIV testing without depending on their husbands or partners. Empowered women can negotiate for safer sex with their partners, reducing the chances of risky sexual behaviors [2]. However, harmful gender norms that enhance male dominance prevent women from exercising their right to negotiate for safe sex and utilize HIV prevention services such as HIV testing, putting them at a disproportionally higher risk of HIV transmission [3].…”
Section: Introductionmentioning
confidence: 99%
“…Sex is most frequent in violent relationships because husbands or partner assert the right to demand sex any time and weaken the power of negotiation of women for safe sex and unwanted pregnancies (Adhena et al, 2020; World Health Organization, 2013). Such power imbalance has been documented as an inhibiting factor against the use of condoms among women (Feyisetan & Oyediran, 2020; Woolfork et al, 2020). Likewise, where wives’ decision making power and knowledge about family planning are limited, the use of contraceptives will not be all-embracing between partners (Do & Kurimoto, 2012).…”
Section: Introductionmentioning
confidence: 99%